2002
DOI: 10.1021/bi0119161
|View full text |Cite
|
Sign up to set email alerts
|

Pentavalent Ions Dependency Is a Conserved Property of Adenosine Kinase from Diverse Sources:  Identification of a Novel Motif Implicated in Phosphate and Magnesium Ion Binding and Substrate Inhibition

Abstract: The catalytic activity of adenosine kinase (AK) from mammalian sources has previously been shown to exhibit a marked dependency upon the presence of pentavalent ions (PVI), such as phosphate (PO4), arsenate, or vanadate. We now show that the activity of AK from diverse sources, including plant, yeast, and protist species, is also markedly enhanced in the presence of PVI. In all cases, PO4 or other PVI exerted their effects primarily by decreasing the Km for adenosine and alleviating the inhibition caused by hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 60 publications
2
77
0
Order By: Relevance
“…This is similar to that found for the Toxoplasma gondii enzyme (2 µM) (Darling et al, 1999) and significantly higher than those measured from human (41 nM) (Spychala et al, Recombinant adenosine kinase from Saccharomyces cerevisiae 1149 1996) or plants (0.3-0.5 µM) AKs (Moffatt et al, 2000). In contrast, a ten-fold higher K m value for A (26 µM) was obtained when whole yeast extract was used as the enzyme source (Maj et al, 2002). These differences could be explained by the dissimilar reaction conditions, including ATP : Mg molar ratio, free ions and pH, that were employed with each yeast enzyme preparation.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…This is similar to that found for the Toxoplasma gondii enzyme (2 µM) (Darling et al, 1999) and significantly higher than those measured from human (41 nM) (Spychala et al, Recombinant adenosine kinase from Saccharomyces cerevisiae 1149 1996) or plants (0.3-0.5 µM) AKs (Moffatt et al, 2000). In contrast, a ten-fold higher K m value for A (26 µM) was obtained when whole yeast extract was used as the enzyme source (Maj et al, 2002). These differences could be explained by the dissimilar reaction conditions, including ATP : Mg molar ratio, free ions and pH, that were employed with each yeast enzyme preparation.…”
Section: Resultsmentioning
confidence: 86%
“…An important feature of AK regulation is its inhibition by high adenosine concentrations. Its dependence on the ATP : Mg 2+ ratio and on the presence of inorganic phosphate and other ions has also been reported (Maj et al, 2000(Maj et al, , 2002. Concerning yeasts, a Saccharomyces cerevisiae AK was purified (Leibach et al, 1971).…”
Section: Introductionmentioning
confidence: 77%
“…Indeed, M. tuberculosis Ado kinase shared more sequence homology with ribokinases than other Ado kinases [10]. Most Ado kinases are monomeric proteins with a molecular mass between 35 and 40 kDa, and their activity is usually stimulated in the presence of inorganic phosphate (P i ) [15,18,19]. In contrast, Ado kinase from M. tuberculosis is a homodimer comprised of identical 35 kDa subunits [10,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…which describes the rate of a bisubstrate reaction where the concentration of an inhibitory substrate A is varied at a fixed concentration of the other substrate [14,15]. For the K m determination of ribose, the concentration of ATP was held fixed at 5 mM, whereas the K m determination of ATP was carried out in the presence of 2 mM ribose.…”
Section: Activity Assaymentioning
confidence: 99%
“…Earlier studies on AK have identified several phosphorylated metabolites and related compounds, which can either activate AK in place of inorganic phosphate or inhibit the enzyme in the presence of phosphate [17,18]. Kinetic and structural studies indicate that these compounds and inorganic phosphate exert their effects by acting on the same regulatory site on the enzyme [14,17,18]. Therefore, it was of great interest to determine whether AK activators and inhibitors had similar effects on RK, which presumably shares a similar catalytic mechanism with AK.…”
Section: Effects Of Ak Activators and Inhibitors On Human And E Colimentioning
confidence: 99%